1986
DOI: 10.1007/bf01243351
|View full text |Cite
|
Sign up to set email alerts
|

On central effects of serotonin re-uptake inhibitors: Quantitative EEG and psychometric studies with sertraline and zimelidine

Abstract: In a double-blind placebo-controlled cross-over study the encephalotropic and psychotropic properties of sertraline--a new potent and highly selective inhibitor of synaptosomal serotonin uptake--were studied along with blood levels of the parent drug and main metabolite in ten normal healthy volunteers. They received randomized at weekly intervals oral single doses of placebo, 100, 200 and 400 mg setraline and 100 mg zimelidine as reference drug. Blood sampling, EEG recordings, psychometric tests and evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 24 publications
5
41
1
Order By: Relevance
“…In the 50 to 300 mg dose range, it exhibited a typical desipramine profile with a marked increase in alpha activity and, even with the highest dose, an increase in beta energies [16,17]. These activating properties were confirmed by improvements in attention and concentration evidenced by psychometric tests [16].…”
Section: Eegmentioning
confidence: 56%
“…In the 50 to 300 mg dose range, it exhibited a typical desipramine profile with a marked increase in alpha activity and, even with the highest dose, an increase in beta energies [16,17]. These activating properties were confirmed by improvements in attention and concentration evidenced by psychometric tests [16].…”
Section: Eegmentioning
confidence: 56%
“…This was surprising, considering the mydriatic effects demonstrated in a study of citalopram [12] and studies of other SSRIs [12,20,21]. The mydriatic effect of SSRIs has previously been explained by an increased sympathetic outflow of noradrenaline [12,21,22], but this may not be the case.…”
Section: Discussionmentioning
confidence: 74%
“…This was surprising, considering the mydriatic effects demonstrated in a study of citalopram [12] and studies of other SSRIs [12,20,21]. The mydriatic effect of SSRIs has previously been explained by an increased sympathetic outflow of noradrenaline [12,21,22], but this may not be the case. Several SSRIs, including escitalopram and citalopram, have actually been demonstrated to decrease the firing activity of the noradrenergic neurons [23,24].…”
Section: Discussionmentioning
confidence: 74%
“…Prior work with "pharmaco-EEG" techniques has shown that the administration of antidepressant compounds yields reproducible changes in EEG activity in healthy control subjects within a few hours of dosing (Saletu et al 1982(Saletu et al , 1983(Saletu et al , 1986(Saletu et al , 1987(Saletu et al , 1987 Grunberger 1985, 1988;Sannita et al 1983;Sannita 1990; …”
Section: Previous Studies Have Shown That Changes In Brain Functionmentioning
confidence: 99%
“…Prior work with "pharmaco-EEG" techniques has shown that the administration of antidepressant compounds yields reproducible changes in EEG activity in healthy control subjects within a few hours of dosing (Saletu et al 1982(Saletu et al , 1983(Saletu et al , 1986(Saletu et al , 1987(Saletu et al , 1987Grunberger 1985, 1988;Sannita et al 1983;Sannita 1990;Itil et al 1984;Herrmann et al 1991;Luthringer et al 1996). The relationship of these immediate EEG changes in control subjects to eventual clinical response in a depressed population is unclear.…”
mentioning
confidence: 99%